Biological Characterization and Evolution of Bacteriophage T7-△holin During the Serial Passage Process - Xu, Hai; Bao, Xi; Hong, Weiming; Wang, Anping; Wang, Kaimin; Dong, Hongyan; Hou, Jibo; Govinden, Roshini; Deng, Bihua; Chenia, Hafizah Y. (Frontiers in Microbiology, 2021)
Bacteriophage T7 gene 17.5 coding for the only known holin is one of the components of its lysis system, but the holin activity in T7 is more complex than a single gene, and some evidence points to the existence of additional T7 genes with holin activity. In this study, a T7 phage with a gene 17.5 deletion (T7-△holin) was rescued and its biological characteristics and effect on cell lysis was determined. Further, the genomic evolution of mutant phage T7-△holin during serial passage was assessed by whole genome sequencing analysis. It was observed that deletion of gene 17.5 from phage T7 delays lysis time and enlarges the phage burst size, however, this biological characteristic recovered to normal lysis levels during serial passage. Scanning electron microscopy showed that the two opposite ends of BL21 cells swell post-T7-△holin infection rather than drilling holes on cell membrane when compared with T7-wt infection. No visible progeny phage particle accumulation was observed inside the BL21 cells by transmission electron microscopy. Following serial passage of T7-△holin from 1st to 20th generations, the mRNA levels of gene 3.5 and gene 19.5 were up-regulated and several mutation sites were discovered, especially two missense mutations in gene 19.5 which indicate a potential contribution to the evolution of the T7-△holin. Although the burst size of T7-△holin increased, high titer cultivation of T7-△holin was not achieved by optimizing the culture process. Accordingly, these results suggest that gene 19.5 is a potential lysis-related component that needs to be studied further, and that the T7-△holin strain with its gene 17.5 deletion is not adequate to establish the high titer phage cultivation process.